2018
DOI: 10.2147/clep.s152168
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery is not associated with celiac disease

Abstract: PurposeThe purpose of this study was to investigate the association between mode of delivery and the risk of celiac disease in two large population-based birth cohorts with different prevalence of diagnosed celiac disease.Patients and methodsThis is an observational register-based cohort study using two independent population cohorts. We used data from administrative registers and health administrative registers from Denmark and Norway and linked the data at the individual level. We included all children who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
0
18
1
1
Order By: Relevance
“…23 Previous studies have suggested that the risk of CID is higher for elective than for acute section. 27,33 Whereas our study has confirmed an increased risk for both acute and elective section, our data is too limited to test for any possible differential risk in the two modes of CS, although the overall estimate is higher for elective CS.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…23 Previous studies have suggested that the risk of CID is higher for elective than for acute section. 27,33 Whereas our study has confirmed an increased risk for both acute and elective section, our data is too limited to test for any possible differential risk in the two modes of CS, although the overall estimate is higher for elective CS.…”
Section: Discussionmentioning
confidence: 52%
“…Large nation-wide populations based studies have evaluated whether the risk of CIDs was increased in CS compared to vaginal delivery. 22,28,33,34 First, an increased risk of IBD was found among 2 mio. children in the Danish population (1973-2008 and 1977-2009, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large registry-based cohort study that included over 1.5 million children from Denmark and Norway found no association between the mode of delivery (cesarean section vs. vaginal birth) and the risk of diagnosed CD (43). Data collected from the same cohort indicated that exposure to systemic antibiotics in the first year of life was positively associated with diagnosed CD, with a dose-dependent relation between an increasing number of dispensed antibiotics and CD risk (44).…”
Section: Early Eventsmentioning
confidence: 98%
“…Similarly, large observational studies found no link between c-section and CeD development ( 49 , 69 , 79 ). Finally, a large register-based study, that included children from two independent cohorts, found that birth delivery mode was not associated with increased risk of diagnosed CeD ( 51 ). Although the data is conflicting, the potential links between early events that can alter the microbiota composition, such as antibiotic use or birth delivery mode, and later CeD implicate a role of the microbiome in disease development.…”
Section: The Role Of Environment In Disease Developmentmentioning
confidence: 99%